Salivary and crevicular fluid interleukins in gingivitis - Boronat-Catalá, Montserrat (Medicina Oral S.L., 2014)
Introduction: Gingivitis is a frequent inflammatory process of the gum tissue that is mainly caused by the accumulation of plaque. The immune response against inflammatory processes is regulated in part by cytokines. Aims: Given that a continuous inflammation exists in gingivitis, it would be logical to assume that the interleukins will be altered locally in those patients. Therefore, the aim of this review was to check whether there is evidence that the interleukins can be used as diagnostic markers of inflammation levels in patients with gingivitis. Materials and Methods: A bibliographical search was undertaken using the key words interleukin and gingivitis in Pubmed, Cochrane, Scopus and Embase. Only those articles published over the last 10 years that were systematic reviews, case-controls or cohort studies in which interleukins in saliva and/or crevicular fluid was investigated in patients with gingivitis were selected. Results: Finally 15 articles were selected, all of them being case-control studies. The interleukins analyzed in the reviewed articles were: IL-1β, IL-8, IL-18, IL-11, IL-12, TNFα, IL-4, IL-17, IL-1α and IL-6. The most commonly studied interleukin is IL-1β and most authors agree that it is higher in the saliva and/or crevicular fluid of patients with gingivitis. Therefore, it could be used as a diagnostic marker of the degree of inflammation in gingivitis. Moreover, as far as the other interleukins studied are concerned, there is no clear consensus among the authors. Conclusion: There is sufficient evidence to suggest that IL-1β in saliva and/or crevicular fluid can be used as a marker of the degree of inflammation in gingivitis. Key words:Interleukins, gingivitis, saliva, crevicular fluid.